The relationship between psychological contract breach and transfer of training at disaster preparedness training in Malaysia civil defense department, Malaysia - Sipon S.; Nazli N.N.N.N.; Zumrah A.R.; Khairudin M.N. (American Scientific Publishers, 2024)
The paper is to identify the relationship between psychological contract breach and transfer of training. There is a lack of study between psychological contract breach and transfer of training among workers in Malaysia. 425 respondents from Malaysia Civil Defense Department, Bangi, Selangor, Malaysia who had attended the Disaster Preparedness training from March to May, 2015 were selected as the sample of this study. The instrument used was Robinsson and Marinsson questionnaire and was analyzed using the quantitative method. The finding of the study showed that there was a strong correlation between the transfer of training and psychological contract breach of the respondents. The majority of the respondents found that psychological contract breach can influence their ability to transfer the knowledge and skills gained from the training to their workplace. 2017 American Scientific Publishers All rights reserved.